2019
DOI: 10.1097/qad.0000000000002045
|View full text |Cite
|
Sign up to set email alerts
|

Genetic complexity in the replication-competent latent HIV reservoir increases with untreated infection duration in infected youth

Abstract: Objective: Timely initiation of combination antiretroviral therapy (ART) limits latent HIV reservoir size and should also limit reservoir genetic complexity. However, the relationship between these two factors remains unclear, particularly among HIV-infected youth. Design: Retrospective analysis of replication-competent latent HIV clones serially isolated by limiting-dilution culture from resting CD4+ T-cell reservoirs from ART-suppressed, young adult participants of a historic phase I therapeutic vaccine tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 44 publications
4
17
0
Order By: Relevance
“…7D. Consistent with previous reports (15), these examples also reveal that HLA-susceptible and -adapted forms of the same CTL epitope commonly coexist in the reservoir: 6 of the 9 subtype B-infected individuals harbored at least one epitope where this occurred.…”
Section: Figsupporting
confidence: 90%
See 1 more Smart Citation
“…7D. Consistent with previous reports (15), these examples also reveal that HLA-susceptible and -adapted forms of the same CTL epitope commonly coexist in the reservoir: 6 of the 9 subtype B-infected individuals harbored at least one epitope where this occurred.…”
Section: Figsupporting
confidence: 90%
“…There, they can persist long term within either the original infected cell or clonal descendants thereof (7)(8)(9)(10). Much of our understanding of HIV persistence is derived from HIV sequences isolated from blood during long-term cART; these studies have revealed that the within-host HIV reservoir is genetically diverse (11)(12)(13), that it frequently contains immune escape mutations (14,15), and that it commonly features clonally expanded cell populations harboring identical proviruses (10,(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Another limitation of this study is that we only included ECs off ART. Thus, we could not match ECs to CPs based on their time on ART, nor did we match ECs to CPs based on their level of diversity or AUC of viremia because this is difficult to control for ( 15 – 17 , 55 , 56 ). Related to the very small reservoir size of ECs, there is limited data on the EC proviral landscape, especially on ART ( 27 , 57 – 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Replication by blood-stage Plasmodium parasites also involves significant epigenetic changes, which are reversed during passage through the mosquito, further underscoring the importance of transmission in counteracting the potentially detrimental effects of within-host selection [34, 35]. This reversal of short-sighted evolution by transmission does require that transmissible varaints not be completely displaced during infection, suggesting that maintaining diversity in a latent viral reservoir [36, 37] or by continuous genetic exchange during colonization [38, 39] are important for ensuring future transmissibility.…”
Section: Discussionmentioning
confidence: 99%